Peran kader posyandu dalam melakukan pendampingan pemberian makan bayi dan anak usia 6-24 bulan - Ahmad Faridi; Mohammad Furqan; Arif Setyawan; Falah Indriawati Barokah (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2020)
The prevalence of nutritional problems in Banten is very high, namely 27,8% stunting and less than 15% nutrition, one of the causes is improper feeding practices for babies and children. The practice of ICF and the activeness of maternal and child health services of cadres in providing assistance to mothers who have children is expected to be able to reduce nutritional problems. This study aims to identify the role of cadres in assisting mothers to practice Infant and Child Feeding (ICF). the research was conducted a cross-sectional study. The sample is cadres of maternal and child health services, who have received training on ICF as many as 30 cadres with a purposive sampling technique. Collecting data using a questionnaire related to the characteristics of cadres including age, education, occupation, length of time as a cadre, and level of knowledge of cadres. Data were analyzed using the chi-square test. As a result, there were 43,3% of cadres who were active in assisting mothers in feeding practices. There is no relationship between characteristics and the role of cadres in providing assistance to mothers of toddlers in providing food (p> 0,05). In conclusion, the characteristics of cadres have no relationship with their role in providing assistance to infant feeding. Cadres can play a more active role in mentoring mothers related to providing food to children.